The key elements of local development - Kisman, Zulfukar Aytac; Tasar, Izzet (Elsevier Science Bv, 2014)
Local Development nowadays is been thought as the key supporting element for the total development and social cohesion. Implementing local development by means of the specific institutions, such as Development Agencies, specially designed and established for this purpose is the most effective and convenient way for accomplishing the expected benefits from local development. Local Development has several reinforcing poles. Without underestimating the other factors important for local development, three main poles can be stated as the most crucial elements for local development, namely the market knowledge and experience, academic ground and internationalisation. Regarding the content and the necessities of local development, these three factors are considerably important. In order to achieve a total development and a beneficial social cohesion, local development is seen as among the most effective path. By well-understanding the key elements for local development and by deploying the accurate and built on purpose institutions, the local development can be succeeded and sustained. (C) 2014 The Authors. Published by Elsevier B.V.
International Conference on Emerging Markets Queries in Finance and Business -- OCT 24-27, 2013 -- Tirgu Mures, ROMANIA
Keywords: Local Development; Development Agencies; Private Sector; Internationalisation